Avaliação das características físicas, sensoriais e nutricionais de biscoitos formulados com batata-doce de polpa alaranjada (Cultivar beauregard) e margarina - Sousa, Laysa Borges Tomas de (2019)
The orange-fleshed sweetpotato (OFSP) is a biofortified food in provitamins A. The addition of this in traditional food products, increases the nutritional value. Fat is an essential ingredient in biscuits and products made with OFSP because of its liposoluble property. In addition, OFSP and margarine have appropriate technological characteristics for the substitution of traditional raw materials in the production of biscuits. Thus, the objective of this work was to study the effect of OFSP:margarine on the characteristics of sensory and nutritional measurements of biscuits. The second order rotational central composite design was used as a method. From these treatments, those who presented higher scores on sensory evaluation and the greater yield on measurements were selected. The selected treatments were characterized for the centesimal composition, retention of total carotenoids and β - carotene. In addition, every 28 days, for 84 days of storage, were evaluated the water activity (aw), pH, total titratable acidity (TTA), carotenoid profile, as well as, the contribution, according to vitamin A requirements in risk groups. The treatments obtained acceptance between 65% and 90% in the sensorial evaluation. OFSP significantly influenced factors such as aroma, color, and appearance. Margarine influenced the texture, flavor and buying intention. The formulations tested showed yields of up to 90% in the measurements. From these results, the treatments T3 (22.23:32.84 g/100 g), T8 (18:34.6 g/100g), and T9 (18:28.57 g/100g) were selected, containing OFSP and margarine, respectively. The biscuits samples containing OFSP (T3, T8, T9) had significantly higher fiber, ash and moisture content than treatment without OFSP. During storage, the biscuits had no modification of pH, TTA, aw, color and hardness. Retention of total carotenoids and β -carotene was higher in T3. There was a significant reduction in the carotenoid profile in storage in all preparations. Biscuits with OFSP addition are a source of vitamin A for the risk groups studied. However, greater contributions were made to vitamin A requirements in the first days of storage. It was concluded that the T3 treatment (22,23:32,84 g/100g) presented better sensorial and nutritional technological characteristics.